P068: Patient satisfaction following educational ultrasounds in the emergency department. (15th May 2017) - Kapur, P.; Betz, M.; Chenkin, J.; Brick, C.
Abstract : Introduction: Development of point-of-care ultrasound (POCUS) image-generating skills requires residents to practice on patients awaiting care in the emergency department (ED) for unrelated reasons. While patients are almost universally agreeable to the scans, there is the possibility that they feel pressured to do so and may have negative experiences that go unreported. The objective of this study was to determine the self-reported patient satisfaction and identify any concerns after educational ultrasounds performed in the ED.Methods: We conducted a survey of patients at a single academic ED. Patients were eligible for enrollment if they had volunteered for an ultrasound when study personnel were available. The survey was administered by a representative from the Patient Affairs Department who advised the patients that the results would remain anonymous and would have no impact on their care. The survey included patient demographics, questions about the consent process, communication by the trainee, adverse reactions and patient satisfaction. The primary outcome was the overall satisfaction level reported by the volunteer patients on a 5-point Likert scale. Secondary outcomes included identification of any discomfort or concerns about the process as expressed by patients. Simple descriptive statistics were used to report survey results.Results: Ninety-nine patients fully completed the questionnaire. Fifty (50%) were women. The age range was 18 to 99 years. Satisfaction among volunteers was high, with 94% of respondents giving a rating of 4 or 5 (five being an excellent experience). No patients gave a negative rating (1 or 2). Three (3%) patients felt "somewhat" pressured to volunteer. A majority of patients (72%) experienced no discomfort during the scan however 16% experienced some physical discomfort. Comments indicated that too much pressure applied with the ultrasound probe or cold ultrasound gel were the main sources of discomfort. Despite some discomfort 95 (95%) patients stated they would likely volunteer again if asked in the future.Conclusion: ED patients volunteering as models for residents learning POCUS expressed generally positive perceptions of their experience. While only a small minority of patients experienced some discomfort or felt pressured into participating, it is important to ensure that patients have a process to communicate any concerns about educational ultrasounds in the ED.